Resilience and Meaningfulness of Life in Broken Home Adolescents - Lia Yohana Santoso; Arthur Huwae (Bisma The Journal of Counseling, 2023)
Living as a broken home child in adolescence tends to have a holistic adverse impact. Broken home adolescents have to go through very difficult and meaningful times. Psychologically broken home adolescents are faced with forming a strong mentality and, as much as possible, interpreting every heavy life event into a meaningful life. This study aims to determine the relationship between resilience and the meaningfulness of life of broken home adolescents. The method used is quantitative with a Spearman rho correlation design. One hundred thirty-five late adolescents aged 18-22 who were in broken homes were used as research participants using an incidental sampling technique. Research measurements used the Resilience Quotient Test (α = 0.874) and the Meaning in Life Questionnaire (α = 0.936). The results prove that resilience is positively and significantly related to the meaning of life of broken home adolescents (r = 0.304 with sig. = 0.000). Resilience contributes 9.2% to the meaningfulness of life. Applying good resilience can help increase the meaningfulness of broken-home adolescents' lives. Future research is expected to design a psychological assistance program according to the broken-home category, to facilitate broken-home adolescents to achieve a healthy life holistically.